2021
DOI: 10.3389/fcvm.2021.638420
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcomes of Three Total Arch Replacement Strategies for DeBakey Type I Aortic Dissection

Abstract: Background: This study employed three surgical techniques: total arch replacement (TAR) with frozen elephant trunk (FET), aortic balloon occlusion technique (ABO) and hybrid aortic arch repair (HAR) on patients with type I aortic dissection in Fuwai Hospital, aiming to compare the early outcomes of these surgical armamentariums.Methods: From January 2016 to December 2018, an overall 633 patients (431 of TAR+FET, 122 of HAR, and 80 of ABO) with type I aortic dissection were included in the study. Thirty-day mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…The two procedures compared in our study significantly differed in such characteristics, as post-operative in-hospital time (20 vs. 24; p = 0.002) and post-operative pulmonary complications (60.4% vs. 83.7%; p < 0.001). Except for the comparable short-term outcomes, the two groups exhibited significant differences in intraoperative variables, in line with the previous studies demonstrating that the HTAR procedure decreased the time of CPB, ACC, as well as the operation duration time ( 20 ). Besides, the use of HTAR via ministernotomy reduced the intraoperatively needed blood transfusion volume.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The two procedures compared in our study significantly differed in such characteristics, as post-operative in-hospital time (20 vs. 24; p = 0.002) and post-operative pulmonary complications (60.4% vs. 83.7%; p < 0.001). Except for the comparable short-term outcomes, the two groups exhibited significant differences in intraoperative variables, in line with the previous studies demonstrating that the HTAR procedure decreased the time of CPB, ACC, as well as the operation duration time ( 20 ). Besides, the use of HTAR via ministernotomy reduced the intraoperatively needed blood transfusion volume.…”
Section: Discussionsupporting
confidence: 89%
“…Since the HTAR approach was first implemented in 2000 by J.A. Macierewicz et al ( 19 ), many cardiovascular centers applied it for over a decade and their data show that HTAR has achieved desirable early and long-term clinical outcomes ( 9 , 20 ). Our method of HTAR via upper ministernotomy procedure has similar indications as the conventional HTAR approach.…”
Section: Discussionmentioning
confidence: 99%
“…In the 7 non-comparative arch zone 2 and proximal studies, one reported both 30-day and in-hospital mortality ( 19 ), four in-hospital ( 18 , 25 , 27 , 28 ) and only two 30-day mortality ( 26 , 29 ). Here, the overall mortality rate ranged from 2.8–9.2% with an average rate of 5.4% ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, pre-existing malperfusion syndromes have been associated with higher mortality after the procedure [44]. In the setting of type A AAD, TAR-FET can be performed with acceptable perioperative outcomes as compared with classical limited repairs in centers with expertise and adequate patient selection [9,45]. A recent meta-analysis of 17 studies, including 1300 patients undergoing TAR-FET for AAD, reported an average in-hospital mortality of 7.8%, ranging from 0% to 18.2% [46].…”
Section: Acute Aortic Dissectionmentioning
confidence: 99%